Reflections of research: united colours of myocytes. (2nd November 2020) - Foldes, Gabor; Talman, Virpi
Abstract : The annual image competition, Reflections of Research, provides a glimpse into the cutting-edge heart and circulatory research funded by the British Heart Foundation